Revisões da masculinidade sob ditadura: Gabeira, Caio e Noll - Idelber Avelar (Estudos de Literatura Brasileira Contemporânea)
This article addresses the coding of masculinity in texts by Fernando Gabeira, Caio Fernando Abreu, and João Gilberto Noll at the turn of the 1970s/1980s. In Brasil the Abertura period coincided with the consolidation of the gay movement, divorce laws, the beginning of the massive incorporation of middle- class women to the wage labor force, increasing visibility of transvestites, and overall the marked decadence of the ideal man promoted by the military regime. This essay discusses the ways in which Gabeira, Caio, and Noll remembered, anticipated, allegorized, cut through, and/or ignored that context, and thus situated themselves in different ways vis-à-vis the revision of masculinity that took place at the turn of that decade. Gabeira wrote a hyperbole that became self-fulfilling, Caio reached the pinnacle of career marked by a methodic erasure of the border between homo- and heteroaffectivity, and Noll inaugurated a three-decade-long reflection on the dissolution of masculinity through the representation of one of its constitutive scenes, the disappearance of the father.